An In-depth Analysis of Trade Interpretations by Abu Hayyan al-Andalusi in al-Bahru al-Muhit: Insights into the Qur'an's Verses on Commerce - Muhamat Nur Maarif; Iskandar Zulqarnain (Global Research Network, 2024)
This paper elucidates the interpretation of Abu Hayyan al-Andalusi in al-Bahru al-Muhit regarding the Verses of Trade. The aim of writing this paper is to explain the concept of trade in the Qur'an, the Verses of Trade in the Qur'an and their interpretation, and the various forms of trade. The sources used in writing this paper include commentary books, articles, and other relevant sources related to the discussion. The results of this paper indicate three terms related to trade in the Qur'an, namely tijarah, bai', and syira'. The term tijarah in the Qur'an is sometimes used to explain the trade relationship between humans and Allah, and sometimes used to describe trade among human beings. Trade among human beings should be based on the principles of mutual consent, transparency in transactions, and the provisions of Islamic law.